Networks of influence: Linking capitals and agency to understand actors’ roles in sustainability interventions - Rölfer, Lena; Isaac, Roman; López-Rodríguez, María D.; Martín-López, Berta; Celliers, Louis; Krause, Gesche (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
In the face of multiple social-ecological crises, the need for sustainability transformations has been widely acknowledged. Understanding how diverse actors influence processes and outcomes—and thus their agency—has been identified as an important lever for sustainability transformations. However, capturing the various dimensions of agency remains challenging. Despite several existing conceptual framings, a clear approach to fully understanding agency within governance networks is still missing. Here, we propose an actor-process network approach to characterize and assess actors’ agency in influencing specific sustainability interventions. Our approach uses network analysis as a methodological bridging element to link the concepts of capitals and agency. We propose five forms of agency: allocating human resources, enacting political relevance, influencing financial flows, providing physical goods and assets, and steering social-ecological discourse. Our approach can contribute to discussions on how to distribute roles and responsibilities between diverse actors involved in sustainability interventions.
Keywords: Agency; Capital; Actor Mapping; Network Analysis; Governance Process; Actor-process Network Approach; Transformation